STATUS OF WOMEN IN TWO BENGALS: EVIDENCE FROM LARGE SCALE SURVEYS - APARAJITA CHATTOPADHYAY and BAISHALI GOSWAMI (J.biosoc.Sci, (2007) 39, 267-286, 2006)
Greater female autonomy is mirrored through better performance in the major demographic and social indicators. This study attempts to capture the effect of religion on the status of women considering `Greater Bengal'. There is much evidence suggesting that when cultural factors are constant, religion does not have a significant effect on any demographic issue. In this paper, the validity of this proposition is examined using two datasets, namely NFHS II (98-99) and BDHS 2000. It is clear from the analyses that not only region but also religion has a distinct effect on the status of women. In West Bengal, the religious gap for all the indicators considered is pretty high, whereas in Bangladesh the gap is not that wide. A state-level population policy is needed in West Bengal to act as a social leveller